Prevalence and potential risk factors for periodontal disease among adults aged 35-54 years in Banten - Theresia, Tiarma Talenta; Putri, Stephanie Lowis (Majalah Kedokteran Gigi Indonesia, 2023)
Periodontal disease is a chronic inflammatory disease that affects the gingival tissue and the underlying structures. Risk factors play a role in both the initiation and development of periodontal disease. It is important to know the risk factors for periodontal disease to prevent the occurrence of more widespread periodontal disease. Based on the 2018 Riskesdas, the prevalence of dental and oral health problems in Banten was 62.8%. This study aims to determine the prevalence and potential risk factors for periodontal disease among adults aged 35-54 years in Banten. This research was an observational descriptive study with a cross-sectional design using secondary data from the 2018 Riskesdas (National Basic Health Research) in Banten. We used total sampling method in this study. Information was processed using SPSS software, and data was presented in tables containing frequencies and percentages. The total number of respondents aged 35-54 years in Banten was 6,755. One thousand eight hundred and sixty-six respondents met the inclusion criteria, while 595 respondents were excluded due to missing data. Thus, 1,271 respondents were obtained and became the research subjects. The majority of respondents were female (64.4%), had low educational level (61.2%), employed (62.6%), brushed their teeth at the wrong time (99.2%), did not smoke (65.9%), did not chew tobacco (96.5%), were obese (51.4%), and did not suffer from diabetes mellitus (95.6%) and hypertension (82.2%). The prevalence of periodontal disease in these respondents was 27.6%. Potential risk factors for periodontal disease among adults aged 35-54 years in Banten include a high degree of education, employment status, smoking behavior, inappropriate toothbrushing time, and obesity.